FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA PEKERJA DI PROYEK PLTGU MUARA TAWAR PT.HUTAMA KARYA TAHUN 2021 - Rika Nurfadhilah (2021)
Hypertension in workers is a disease that can be caused by work and lifestyle of workers. Adverse lifestyle and behavioral factors such as smoking habits, coffee consumption habits are the causes of the risk for hypertension among workers. The purpose of this study was to determine the factors associated with the incidence of hypertension in the PLTGU Muara Tawar PT. Hutama Karya 2021. This type of research uses quantitative analytics with a cross-sectional study design. The population in this study were 148 workers and the minimum sample size was 118 workers. When the research started from November 2020 to January 2021. Data analysis in this study was in the form of univariate analysis and bivariate analysis using the chi square test. The results in this study found that 52.5% of workers had hypertension. The results of the analysis on the statistical test showed that age (P-value = 0.002), family history (P-value = 1,000), BMI (P-value = 0.014), coffee consumption habits (P-value = 0.972), smoking habits (P- value = 0.011), sleep duration (P-value = 0.023), work stress (P-value = 0.673). Therefore, workers are advised to regulate the intake of foods that are low in fat and nutritious, have adequate sleep and reduce cigarette consumption. Keywords : Factors, Hypertension, Project Workers, Coffee, Job Stress.